Transformasi Kurikulum dan Trandar Kompetensi SMK dalam Era Merdeka Belajar - Kuncahyono Kuncahyono; Nur Cholis; Akhyar Basyir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the strategic role of Vocational High Schools (SMK) in preparing a skilled workforce amid global dynamics and rapid technological developments. The focus of the discussion lies in the implementation of the Independent Curriculum which provides flexibility for educational units to develop learning that is contextual, adaptive, and relevant to the needs of the world of work. Through strengthening the project-based learning approach, teaching factory, and collaboration with industry, the Merdeka Curriculum encourages harmony between learning in vocational schools and competencies needed by the business world and the industrial world (DUDI). This article analyzes curriculum documents, learning outcomes, and Graduate Competency Standards (SKL), and identifies a number of challenges in implementation, such as inequality of facilities, limited involvement of DUDI, uneven teacher capacity, and regulatory complexity. By referring to regulations such as Permendikbudristek No. 12 of 2024 and Presidential Instruction No. 9 of 2016, the author proposes systematic steps such as competency mapping, preparation of Learning Objectives Flow (ATP), and evidence-based evaluation. The transformation of vocational education through collaboration between stakeholders is expected to create an educational ecosystem that is responsive to industrial and technological changes. This article concludes that vocational schools must be able to become institutions that not only produce job-ready graduates, but also innovative and creative in creating new job opportunities.